Graphic Design Campaigns For Environmental Awareness: Reducing Plastic Bag Usage In Palestine A Preliminary Review - Mohammed Asad, Mahmoud Salama; Ibrahim Waseif, Ahmed Husain (Journal of Neonatal Surgery, 2025)
Single-use bag pollution is a rising menace to the sustainability of the environment in developing countries as the enforcement of environment of laws is not enforced to the fullest measure. The following paper indicates a thematic review of the influence of environmental awareness campaigns and in particular those that employ the use of graphic design in raising the awareness of the population and changing the behaviours associated to the use of plastic bags. Applying to the Palestinian reality, the review summarises the literature on world and regional awareness campaigns, the role of visual communication, and the science of behaviour, which leads to societal participation. Three important findings show that there is disjunction between the environmental knowing and the observed behavioural change whereby culturally-adapted visually effective and emotion appealing advertising campaigns are required. The review also finds that there were severe gaps in research and the need to have integrated approaches that used combinations of policy, education and creative advocacy. This piece of work is not only valuable in the scientific discussion, but also valuable in ways of proceeding in a sustainable environmental behaviour using the communication design.